Characteristics of anthropogenic solid waste in some mangrove ecosystems of East Java, Indonesia - Retnaningdyah Catur; Vidayanti Viky (BIO Web of Conferences)
Some mangrove ecosystems in East Java, Indonesia have a serious problem, i.e. the degradation of ecosystem quality caused by anthropogenic solid waste pollution dominated by macroplastics from human activities in the surrounding area. This study aimed to evaluate the characteristics of anthropogenic solid waste trapped in the mangrove ecosystem and its impact on changes in the qualities of water and sediment. This research used the ex post facto method in ten mangrove ecosystems of East Java with different anthropogenic activities including Trenggalek (Cengkrong), Malang (Gedangan and Kondang Merak), Pasuruan (Penunggul), Probolinggo (Pantai Duta), Situbondo (Dubibir and Blekok), Surabaya (Gunung Anyar and Medokan Ayu) and Banyuwangi (Alas Purwo National Park/APNP). At each location, anthropogenic solid waste was monitored, including plastic, metal, glass, rubber, paper, cloth, and other waste, by making three plots with each size of 5 x 1 m2. The research results showed that the density ratio of plastic to non-plastic anthropogenic waste in ten mangrove ecosystems in East Java was 55:45. The mangrove ecosystems in Dubibir, Penunggul, and Cengkrong have moderate anthropogenic solid waste. The mangrove ecosystems in Kondang Merak, Gedangan, Duta, Medokan Ayu, and Gunung Anyar have low to moderate anthropogenic solid waste densities. The mangrove ecosystem in APNP has the lowest anthropogenic solid waste density. Based on the results of data analysis, it can be seen that high human activity will have an impact on increasing anthropogenic solid waste. Thus, solid waste management in the mangrove ecosystem is needed to control human activities around the mangrove ecosystem. Sampling was carried out in 11 mangrove ecosystems of Sawahmulya.